Analisis Minat Berinvestasi Generasi Z (Net Generation) UIN Suska Riau Pada Pasar Modal Dari Perspektif: Literasi Keuangan, Motivasi Investasi Dan Teknologi Informasi - Aira, Aras; Fauzana, Riri; Djamil, Nasrullah (Politeknik Ganesha Medan, 2024)
The aim of this research is to determine the influence of financial literacy, investment motivation and information technology on the interest of Generation Z Uin Suska Riau to invest in the Indonesian Capital Market. Research was conducted on students and female students at Uin Suska Riau, the sampling technique used in this research was puposive sampling, using several criteria, namely students who were sampled were students and female students who had opened a stock account on the Indonesian capital market. Data was taken from students who registered in the Uin Suska Riau Investment Gallery. Data processing using SEM_PLS with Smart PLS Version 3. The results of the research show that the results of the Path Coefficient test for the three variables, namely financial literacy, investment motivation and information technology, have a positive value on Generation Z Uin Suska's interest in investing in the capital market, from the results of the hypothesis test. carried out, it can be concluded that financial literacy has an influence on Uin Suska Riau generation Z's interest in investing, but investment motivation and information technology have no influence on generation Z's investment interest. Keywords: : Generation Z interests; Financial literacy; investment motivation and information technology;investment interest.